Morfologia do encéfalo de emas (rhea americana americana linnaeus, 1758) - Costa, Herson da Silva (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this study was to identify macroscopically the regions of the brain, as well as the cerebral arteries and the cerebral arterial circuit, in order to establish a vascular pattern and its systematization, as well as to quantify its morphometry and stereology. In order to do so, 21 greater rhea brains were used, 13 females and 2 males (ages 18 months) and 4 females and 2 males (ages 2 months) for the study of vascularization and 22 encephalus, 2 females and 1 male (1 month), 1 female and 2 male (2 months), 2 females and 1 male (3, 4, 5 and 6 months) and 2 females and 2 males (18 months) for morphometry and stereology analyzes. The animals were thawed and incised in the sagittal plane, in the cervical region, in order to expose the left common carotid artery, which was cannulated and the vascular system washed with 0.9% saline, and then perfused with Neoprene latex 650, stained with red pigment, in order to allow a better visualization of the arteries. For the morphometric and stereological study, the carotids were cannulated and perfused with about 5-10 ml of 3.7% formaldehyde in order to obtain the fixation of the brains. Subsequently, the pieces were immersed in aqueous solution of 3.7% formaldehyde for 72 hours, and then, dissections and removal of the bones from the skull cap were initiated. Then, the brains were analyzed, and the structures were identified, measured, photographed, schematized and nominated. As for stereology, the brains were included in colorless gelatin, held in refrigerator for 24 hours, and subsequently cut 4 mm thick. Gelatin was then removed, Mainland stained and quantification of brain volume was performed (V = T. a / p. Σpi). The brain was divided into: telencephalon, diencephalon, brain stem and cerebellum, and, externally, olfactory bulbs, optic lobes, optic nerves, optic chiasm, pituitary and pineal were observed. Ventral spinal, basilar, ventral cerebellar, mid-ventricular cerebellar, caudal branches of the carotid arteries of the brain, ventral mesencephalic arteries, caudal cerebral arteries, carpal arteries of the brain, middle cerebral arteries , cerebroethmoidal, rostral intercerebral anastomosis, cerebellar rostrais, ethmoidal, internal ophthalmic, interhemispheric, pituitary, dorsal mesencephalic, dorsal cerebellar, occipital, pineal and dorsal hemispherical branches. The cerebral arteriosclerotic circuit was closed, caudally and rostrally in 100% of the specimens. The brain had measurements that reached up to 50.267 mm in length, 41.855 mm in width, 29.320 mm in height and 21.774 g in mass. Optical lobes presented values of right length (12.647 mm), left length (12.355 mm), right width (11.470 mm), left width (10.827 mm) and right height (15.495 mm) and left height (15.112 mm). The cerebellum presented values of up to 21.462 mm (length), 18.207 mm (width) and 21.487 mm (height). As to the stereology of the encephalon, this varied from 33.663 cm³ and 71.971 cm³ (ages 1-18 months), respectively
Keywords: Vascularização; Morfometria; Estereologia; Aves; Ratitas; Vascularization; Morphometry; Stereology; Birds; Ratites; CIENCIAS AGRARIAS::MEDICINA VETERINARIA